The walking dead. The complete second season [videorecording (DVD)] - Darabont, Frank; Holden, Laurie; Lincoln, Andrew, 1973-; DeMunn, Jeffrey, 1947-; Callies, Sarah Wayne, 1977-; Bernthal, Jon; Kirkman, Robert (Walking dead (TV series) ;), 2012)
'The Walking Dead' is a drama where personal struggles are magnified against a backdrop of crises. The series explores how the living are changed by the realization that those who survive can be far more dangerous than the walking dead.